Implementation Of Local Regulations For Village Development - Tika Widyana Pratiwi; Siti Rodhiyah Dwi Istinah (UNISSULA Semarang, 2021)
This study aims to identify and analyze the implementation of regional regulations regarding village development policies and the factors and obstacles that affect village development. The approach method used in this research is a sociological juridical approach.The Regional Regulation on village development policies regulates Village Development. As mandated by Law Number 6 of 2014 concerning Villages and Government Regulation Number 43 concerning Guidelines for the Implementation of the Village Law, namely the realization of an advanced, independent, prosperous Village without losing its identity. In practice, sometimes what is being carried out is not in accordance with what is aspired so that in this study the author wants to know how to implement Regional Regulations regarding village development policies, what factors and obstacles affect village development in the region by using normative juridical research methods. As for the facts found that the implementation of regional regulations on village development policies has not been fully implemented. Resources are critical to effective policy implementation. In implementing the Regional Regulation on village development policies, there are still obstacles related to the availability of resources. Regional regulations regarding village development policies are actually directed at efforts to bring about change in society for the better. These changes will be successful if the community has the resources and attitudes that are conducive to policy.